Molecular Mechanics and Semi-empirical Analysis of the Interaction Between Co2+ and the Amino Acids in Solution in Water - Huq, Fazlul; C.R. Peter, Marie (Asian Journal of Chemistry, 2010)
The interaction between Co2+ and amino acids, viz., L-histidine and L-arginine in solution in water has been investigated by UV-visible spectrophotometry using the technique of continuous variation and molecular modeling. For the metal ion and the two amino acid combinations, absorbance values at λmax were plotted against concentrations of reactants. The maxima in the absorbance vs. concentration graphs gave the ratios at which the metal ion and amino acids combined. Cobalt(II) is found to form predominantly 1 : 4 complex with Lhistidine and 1 : 3 complex with L-arginine. The proposed structures of the complexes have been optimized and their electronic spectra generated based on molecular mechanics and semi-empirical calculations. Comparison of the observed and predicted electronic spectra suggested the most likely structures present in solution.